2020
DOI: 10.1002/cnr2.1258
|View full text |Cite
|
Sign up to set email alerts
|

Effect of renal function on neutrophil decreases following eribulin administration

Abstract: Background: Eribulin therapy has recently attracted attention from various viewpoints, including quality of life, and is considered a standard therapy for inoperable or recurrent breast cancer. Although a reduction in renal function reportedly decreases total eribulin clearance, its association with dose-limiting toxicity and the reduction of neutrophils remain unclear. Aim: This study was aimed at analyzing the association between decreased renal function prior to eribulin administration and the occurrence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 17 publications
0
0
0
Order By: Relevance
“…In their logistic analysis, the authors used at baseline (<2,900), which had a decisive influence on the results. A previous study reported that a baseline neutrophil count of <3,000 was a risk factor for severe neutropenia, which supports our results (10,12). High AST and bilirubin levels are risk factors for liver dysfunction.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In their logistic analysis, the authors used at baseline (<2,900), which had a decisive influence on the results. A previous study reported that a baseline neutrophil count of <3,000 was a risk factor for severe neutropenia, which supports our results (10,12). High AST and bilirubin levels are risk factors for liver dysfunction.…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, we considered it theoretically consistent that high AST and bilirubin levels were identified as risk factors in this study. Furthermore, creatinine clearance <50 ml/min alone was not identified as a risk factor for severe neutropenia in this study, although it has been reported as a risk factor for severe neutropenia in prior renal function-adjusted studies (12). However, in an additional validation of this study, the frequency of severe neutropenia was 80% when the drug was used at 100% without a dose reduction in creatinine clearance of <50 ml/min; whereas the incidence decreased to 17% when the dose was reduced.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation